The Effectiveness of two Types of Feedback (Recast, and Metalinguistic) on Improving the 8th Grade Basic Students' Performance in Arabic Grammar - Maqableh, Nasr; Al-Zeout, Mohammad; Al-Zeout, Mohammad (Jordan Journal of Educational Sciences, 2015)
The study aimed to identify the effectiveness of two types of Written corrective Feedback: (Recast and Metalinguistic) on improving the students' performance in Arabic Grammar. The researchers constructed a test that measured the performance of the students in grammar according to Bloom’s three Levels: knowledge, comprehension, and application.The sample of the study consisted of (74) students. The students were assigned into three groups. The study was conducted as the intervention was administered in the form of (18) periods. The first experimental group participants received a recast; the second experimental group participants received the Metalinguistic, while the control group did not receive Written Corrective Feedback. The results of the study showed that there was a significant difference at (α= 0.05) in the students' performance on Bloom's three levels between the three groups participants’ performance. These differences were in favor of the two experimental groups. Moreover, the results of the study showed a significant difference in the students' performance on the application level between the experimental groups in favor of the students in the first experimental group. The results also showed a significant difference in students' performance in the grammar test as a whole in favor of the students in the two experimental groups